Participatory design and evaluation of digital coaching for improving health—the star multicomponent lifestyle intervention - Lindgren, Helena; Kilic, Kaan (Frontiers in Digital Health, 2025)
IntroductionThere are particular challenges when designing and developing a digital coaching application aimed at providing person-tailored support for lifestyle changes in multiple domains to promote health. This study explored how a participatory design process addresses challenges that materialised in a multicomponent lifestyle intervention, providing an understanding of the onboarding experience and early user engagement.MethodA participatory design methodology was applied involving a multidisciplinary team of 12 domain experts and different groups of end users in design cycles, model construction, prototyping, and evaluation. The process followed a design methodology for argument-based health information systems and a framework for layered interactive adaptive systems to engage domain experts in the development of aspects relating to the interactivity of the system. A qualitative user study was conducted with eight participants, five regular users and three nurses, focussing on the onboarding phase.ResultsContributions of this article are (i) the StarCoach, the person-tailored health-promotion intervention for multiple health behaviours supporting short and long-term goals; (ii) a framework for studying multicomponent lifestyle interventions with multiple behaviour change techniques (BCTs); and (iii) qualitative results regarding usage, adherence to, and perceived effects of the intervention with a focus on the initial phase of using the application. The five regular participants reported increased health-promoting activities during the onboarding phase and were using already habituated activities to establish a routine to use the intervention.ConclusionThe participatory design led to StarCoach embedding clusters of BCTs, which build a framework for research on multicomponent lifestyle interventions. Whether using already habituated activities to establish a routine to use the intervention could be a strategy to increase adherence and engagement in the onboarding phase and beyond will be a focus in future studies. The participants also showed increased engagement in their chosen lifestyle-change activities during the study period. The findings will be followed up in future studies to evaluate the effects on behaviour over a longer period of time.